mTOR Modulates the Endoplasmic Reticulum Stress-Induced CD4+ T Cell Apoptosis Mediated by ROS in Septic Immunosuppression - Hao Wang; Jianwei Chen; Guangxu Bai; Wen Han; Ran Guo; Na Cui (Mediators of Inflammation)
Introduction. When sepsis attacks the body, the excessive reactive oxygen species (ROS) production can result to endoplasmic reticulum stress (ERS) and eventually cause lymphocyte apoptosis. The mammalian target of rapamycin (mTOR) is essential for regulating lymphocyte apoptosis; we hypothesized that it mediates CD4+ T cell apoptosis during ROS-related ERS. Method. We, respectively, used ROS and ERS blockers to intervene septic mice and then detected ERS protein expression levels to verify the relationship between them. Additionally, we constructed T cell-specific mTOR and TSC1 gene knockout mice to determine the role of mTOR in ROS-mediated, ERS-induced CD4+ T cell apoptosis. Results. Blocking ROS significantly suppressed the CD4+ T cell apoptosis associated with the reduction in ERS, as revealed by lower levels of GRP78 and CHOP. ERS rapidly induced mTOR activation, leading to the induction of CD4+ T cell apoptosis. However, mTOR knockout mice displayed reduced expression of apoptotic proteins and less ER vesiculation and expansion than what was observed in the wild-type sepsis controls. Conclusion. By working to alleviate ROS-mediated, ERS-induced CD4+ T cell apoptosis, the mTOR pathway is vital for CD4+ T cell survival in sepsis mouse model.